SYNTHESIS OF CALCIUM CARBONATE (CaCO3) FROM EGGSHELL BY CALCINATION METHOD - Diningsih, Candra; Rohmawati, Lydia (Universitas Mataram, 2022)
Calcium is an essential nutrient the human body needs to control blood pressure and maintain strong bones and teeth. One type of calcium that is often consumed and safe for health is calcium carbonate. It can obtain this material from chicken eggshell waste, where it is known that the CaCO3 content is 95%. Therefore, it conducted this research to see the phase, functional group, absorbance level, and energy band gap of CaCO3 samples. CaCO3 was synthesized using the calcination method, in which the egg shells were first soaked in sodium hypochlorite, then dried at 250Â°C for 10 minutes, and CaCO3 powder was obtained. Then the powder was characterized by XRD, FTIR, and UV-Vis. The results of XRD analysis showed that the calcite phase of CaCO3 was 100% according to the JCPDS PDF of calcite (96-901-6707) with a crystalline size of CaCO3 of 22.6 nm. The results of FTIR of CaCO3 samples at the absorption peak of 4000-500 cm-1 identified the functional groups of Ca-O, C-O, -CH2, and O-H. CaCO3 samples can absorb light at wavelengths of 237.1 nm, 251.5 nm, and 289.7 nm, which have an energy band gap of 3.91 eV. Thus, using this simple calcination method, the CaCO3 sample obtained from the extraction of chicken egg shells can later be applied in the medical field.